Functional Changes of the Community of Microbes With Ni-Dependent Enzyme Genes Accompany Adaptation of the Ruminal Microbiome to Urea-Supplemented Diets - Lu, Zhongyan; Xu, Zhihui; Kong, Lingmeng; Shen, Hong; Aschenbach, Jörg R. (Frontiers in Microbiology, 2020)
Urea is an inexpensive non-protein nitrogen source commonly supplemented to the diets of ruminants. It is cleaved to ammonia by bacterial ureases, which require Ni as a catalyst for ureolysis. The key event in the changes of the ruminal microbiome after urea supplementation remains unknown. We have therefore investigated changes in the ruminal microbiome and its community with Ni-dependent enzyme genes following urea supplementation and analyzed the associations of rumen environmental factors, including fermentation variables and Ni concentrations, with the compositional and functional changes of these communities. We found that urea supplementation increased urease activity and the concentrations of ammonia and Ni, and tended to increase concentrations of short chain fatty acids and acetate, whereas it decreased rumen pH and the L-/D-lactate ratio. With standards for genome completeness > 60% and strain heterogeneity < 10%, 20 bacterial species containing five Ni-dependent enzyme genes were detected in the metagenome sequences. For the five Ni-dependent enzyme genes, urea supplementation increased the relative abundances of genes of urease and acetyl-CoA synthase, whereas it decreased the relative abundances of genes of glyoxalase I, [NiFe]-hydrogenase, and lactate racemase. For the 20 microbes with Ni-dependent enzyme genes, urea supplementation increased the relative abundances of five bacteria exhibiting high capacities for the utilization of hemicellulose and pectin for butyrate and fatty acid biosynthesis. For the ruminal microbiome, urea supplementation increased the metagenomic capacities for hemicellulose and pectin degradation, butyrate generation, fatty acid biosynthesis, and carbon fixation, whereas it decreased the metagenomic capacities for starch degradation, propionate generation, and sulfur and nitrogen metabolism. Constrained correspondence analysis identified rumen ammonia and Ni concentrations as likely driving factors in the reshaping of the ruminal microbiome and, together with pH, of the community of microbes with Ni-dependent enzyme genes. Thus, the functional change of the latter community is probably an important event in the adaptation of the ruminal microbiome to urea-supplemented diets. This result provides a new perspective for the understanding of the effects of urea supplementation on rumen fermentation.